Phosphorylation of the Drosophila adherens junction protein Armadillo: Roles for Wingless signal and zeste-white 3 kinase. - Peifer, M.; Pai, L.M.; Casey, M. (Developmental Biology, 1994)
The Drosophila segment polarity gene product Armadillo provides a link between two seemingly separate processes, regulation of segmental pattern by the Wingless intercellular signal and the function of cell-cell adherens junctions. armadillo was originally identified because of its segment polarity phenotype but subsequently was found to be the homolog of the vertebrate adherens junction protein beta-catenin. We examined the nature of the post-translational modification of Armadillo and its possible role in regulating Armadillo function. Armadillo is a phosphoprotein. Its level of phosphorylation varies both during embryonic development and from tissue to tissue. Phosphorylation occurs on both serine or threonine and tyrosine residues. Finally, Wingless signal negatively regulates Armadillo phosphorylation, while the segment polarity gene product Zeste-white 3, a serine/threonine protein kinase, promotes Armadillo phosphorylation. We discuss the implications of these results for regulation of Wingless/Wnt-1 signaling and adherens junction function.